Healthy Monitoring and Fault Detection Outer Race Bearing in Induction Motor Using Stator Current - Iradiratu Diah P K; Belly Yan Dewantara; Wahyu Mulyo Utomo (International Journal of Integrated Engineering, 2019)
This paper describes a new method for monitor and detection bearing damage on induction motor. This is considered important because induction motors have an important role in the industry which functions as the main engine in the production process. This paper focuses on bearing damage because this is the most common case. the case of damaged bearing is done by giving the outer race bearing hole in three cases, 1 mm hole, 2 mm hole and 3 mm hole. Bearing damage analysis is carried out through a stator current signal on an induction motor, then the Fast Fourier transform (FFT) algorithm is used to see the characteristics of the frequency spectrum that appears in the stator current signal. High frequency analysis is applied to get clear analysis results. The results obtained by analyzing the frequency spectrum in the stator current that bearing damage indicate there is an amplitude that appears in the sideband frequency